2015
DOI: 10.1108/s1085-462220150000016001
|View full text |Cite
|
Sign up to set email alerts
|

Is Intelligent Online Tutoring Software Useful in Refreshing Financial Accounting Knowledge?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The implementation and validation of the ITS presented in the studies usually took place over short-term periods (a course or a semester) and no longitudinal studies were identified, except for the study by Jackson and Cossitt (2015). On the other hand, most of the studies showed (sometimes slightly) positive / satisfactory preliminary results regarding the performance of the ITS, but they did not take into account the novelty effect that a new technological development could have in an educational context.…”
Section: Intelligent Tutoring Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation and validation of the ITS presented in the studies usually took place over short-term periods (a course or a semester) and no longitudinal studies were identified, except for the study by Jackson and Cossitt (2015). On the other hand, most of the studies showed (sometimes slightly) positive / satisfactory preliminary results regarding the performance of the ITS, but they did not take into account the novelty effect that a new technological development could have in an educational context.…”
Section: Intelligent Tutoring Systemsmentioning
confidence: 99%
“…Teaching course content Most of the studies (n = 4) within this group focused on teaching Computer Science content (Dobre, 2014;Hooshyar, Ahmad, Yousefi, Yusop, & Horng, 2015;Howard, Jordan, di Eugenio, & Katz, 2017;Shen & Yang, 2011). Other studies included ITS teaching content for Mathematics (Miwa et al, 2014), Business Statistics and Accounting (Jackson & Cossitt, 2015;Palocsay & Stevens, 2008), Medicine (Payne et al, 2009) and writing and reading comprehension strategies for undergraduate Psychology students (Ray & Belden, 2007;Weston-Sementelli, Allen, & McNamara, 2018). Overall, these ITS focused on providing teaching content to students and, at the same time, supporting them by giving adaptive feedback and hints to solve questions related to the content, as well as detecting students' difficulties/errors when working with the content or the exercises.…”
Section: Intelligent Tutoring Systemsmentioning
confidence: 99%
“…Halabi and Larkins (2016) found that posting on discussion forums had a positive effect on performance outcome. Further, provision of access to online resources such as discussion forums has been proven to be effective in enhancing intellectual and collaborative engagement between on‐ and off‐campus students (Bongey et al , 2005; Chou and Min, 2009; Jackson and Cossitt, 2015). However, scant attention has been paid to exploring the effect of specific types of engagement strategies using collaborative discussion forums on performance outcomes.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…During the second half of the first and second decades of this century, as web-based technologies grew in sophistication and incorporated facilities for interactivity, individualization and adaptivity, accounting education research embraced more nuanced explorations of learner experiences. For example, later CMA research saw more in-depth studies of affordances for Web-based assessment within online systems (Apostoulou, Blue & Daigle, 2009;Einig, 2013;Potter & Johnston, 2006), web-based homework Phillips & Johnson, 2011) and online tutoring software (Jackson & Cossitt, 2015). Other salient research in this period included the examination of the effects of various types of online tests (Camp, Earley & Morse, 2015), such as multiple-choice questions (Einig, 2013;Simkin, Keuchler, Savage & Stiver, 2011) on student learning.…”
Section: Two Waves Of Cma Researchmentioning
confidence: 99%